Evolusi Konsep Ruang Hijau Publik di Kota Semarang pada Awal Abad ke 20 Hingga Sekarang (Ruang Hijau Publik di Kawasan Candi Baru) - Wulansari, Katiti (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
According to BNPB (2010), Merapi eruption has destroyed 3.705 units of house in Central Java Province and 3.424 units of house in D.I Jogjakarta Province. Klaten is the most affected area In Central Java, approximately 501 ha of land had degraded and covered by volcanic ash in Balerante Village. While the severely damaged settlements impacted by the eruption reached 496 ha (BNPB, 2010). The research is made to comprehend GIS model on finding alternative locations for impacted settlement in hazardous zones of eruption. The principal objective of the research study is to identify and analyze physical condition, community characteristics, and local government regulation related to settlement relocation plan for impacted area of eruption. From the analyses found that priority relocation areas approved by the natural physical, governmental and community aspects are Tegalmulyo as the first priority with 35.9 ha area, Kendalsari as the second priority with 20.1 ha, and Talun as the third priority with 26.8 ha.